Plasmacytoid dendritic cells and type I interferon in the immunological response against warts. (24th July 2017) - Saadeh, D.; Kurban, M.; Abbas, O.
Summary : Background: Plasmacytoid dendritic cells (pDCs) are the most potent producers of type I interferons (IFNs), and are involved in the pathogenesis of several cutaneous infectious (especially viral), inflammatory/autoimmune and neoplastic entities. Their role in the pathogenesis and regression of human papilloma virus (HPV)‐induced skin lesions has not been well studied. Aim: To investigate pDC occurrence and activity in HPV‐induced skin lesions, including inflamed and uninflamed warts as well as epidermodysplasia verruciformis (EDV)‐associated lesions. Methods: In total 20 inflamed and 20 uninflamed HPV‐induced skin lesions (including 7 EDV lesions) were retrieved from our database, and the tissue was immunohistochemically tested for pDC occurrence and activity using anti‐BDCA‐2 and anti‐MxA antibodies, respectively. Results: pDCs were present in all 20 inflamed warts and absent from all 20 uninflamed cases. MxA expression was also diffuse and strong in 75% (15/20) inflamed warts, but not in any of the uninflamed warts. Conclusions: pDCs constitute a central component of the inflammatory host response in inflamed warts, possibly contributing to their regression through production of type I interferons.